Brief Presentation of Near-field Test Application in EMC Diagnostic - HOU De-chao; SHAO Rui; YANG Tian-fan (机车电传动)
According to the problem of EMI source hard positioning in EMI test, a near-field diagnostic test systems was presented with different dimension and type near-field probe to position larger radiation point accurately, which provided a fast and effective positioning method to complete radiation EMI fault diagnostic and guided practical application.